Características del acoso sexual callejero en las alumnas del X ciclo de Trabajo Social de la UNT – 2018. - Mendoza Guzmán, Anarosa Jesús (2019)
The present investigation was carried out with the general objective of determining what are the characteristics of street sexual harassment in the students of the X cycle, of the EAP Social Work, in the year 2018. It is a descriptive study, applied with a non-experimental design, whose sample population was constituted by 47 students selected at random. For the development of this research we used tools such as: surveys on the characteristics of the ASC, which are mostly men to women and physical, verbal and non-verbal manifestations, as well as instruments such as questionnaire of closed questions, and some with multiple answers, is in this way that seeks to obtain the necessary information and evaluate the problem posed. For a better study, the information resulting from the applied surveys was divided, taking as a first point the general characteristics of the students, such as their age range and the district of their resident. As a second point, all the pictures referring to the manifestations of harassment are described and analyzed, which occurs mostly on the part of men towards women, in which the possible feelings and perceptions of the ASC in the students were evaluated. , the characteristics of the bullies according to the students, as well as the consequences of street sexual harassment. In the third point we have the study of the ways in which sexual street harassment occurs in young students, which was assessed as manifested physically, verbally and non-verbally. And it culminates with conclusions and suggestions, of all the research carried out.